2021
DOI: 10.3389/fphys.2021.773055
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the Role of Ferroptosis in Fluorosis

Abstract: As a strong oxidant, fluorine can induce oxidative stress resulting in cellular damage. Ferroptosis is an iron-dependent type of cell death caused by unrestricted lipid peroxidation (LPO) and subsequent plasma membrane rupture. This article indicated a relationship between fluorosis and ferroptosis. Evidence of the depletion of glutathione (GSH) and increased oxidized GSH can be found in a variety of organisms in high fluorine environments. Studies have shown that high fluoride levels can reduce the antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Since the discovery of ferroptosis, its toxic mechanism regarded as exogenous chemicals has attracted extensive attention. However, the pathogenesis of ferroptosis in fluorosis is not clear, and the key genes and pathways related to ferroptosis in fluorosis need to be further discovered [ 19 ]. In this study, 35 differentially expressed genes (17 upregulated and 18 downregulated) related to ferroptosis in fluorosis were obtained by analyzing the gene expression profile of the fluoride exposure model for the first time and were used to indicate that ferroptosis-related genes are involved in the pathogenesis of fluorosis, suggesting potential pharmacological targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the discovery of ferroptosis, its toxic mechanism regarded as exogenous chemicals has attracted extensive attention. However, the pathogenesis of ferroptosis in fluorosis is not clear, and the key genes and pathways related to ferroptosis in fluorosis need to be further discovered [ 19 ]. In this study, 35 differentially expressed genes (17 upregulated and 18 downregulated) related to ferroptosis in fluorosis were obtained by analyzing the gene expression profile of the fluoride exposure model for the first time and were used to indicate that ferroptosis-related genes are involved in the pathogenesis of fluorosis, suggesting potential pharmacological targets.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent KEGG pathway analysis found that the differential expression of ferroptosis-related genes in fluorosis is mainly involved in ferroptosis, fatty acid metabolism, and glutathione metabolism. Besides that, in a fluoride-containing medium, the degree of ferroptosis of sub-cultivating MC3T3-E1 (WT) cells was higher than that of fluoride-resistant MC3T3-E1 (FR) cells, indicating that there is a potential link between fluorosis and ferroptosis [ 19 ]. In addition, a cross-sectional study of schoolchildren reported that Glutathione S-Transferase (GST) levels were positively associated with the degree of fluorosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of the iAs methylation pattern may be influenced by GSH depletion reported by iF exposure [ 39 ]. It has already been shown that GSH depletion could be a potential mechanism associated with altered methylation capacity [ 17 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis activators like erastin or RSL3 cease the antioxidant system once they enhance the deposition of iron inside the cell [ 129 ]. The iron deposited over here will directly produce excessive ROS via the Fenton reaction, leading to an increase in OD [ 130 ]. Moreover, the activity of enzymes namely LOX or Egg-laying defective nine (EGLN) prolyl hydroxylases is increased by iron accumulation, where the roles of the enzymes are LiPr and oxygen homeostasis respectively [ 49 , 94 , 131 , 132 ].…”
Section: Hallmarks Features Of Ferroptosismentioning
confidence: 99%